2014
DOI: 10.11564/0-0-625
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Marriage and First Birth Interval in Ethiopia: Analysis of the Roles of Social and Demographic Factors

Abstract: The ages at which females establish marital union and give first birth depend on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 17 publications
12
32
0
Order By: Relevance
“…Comparison of our findings with the few published studies from Ethiopia is not warranted due to methodological differences as well as the amount and nature of data used in our analyses. Nevertheless, there are indications from previous studies in Ethiopia of a decline in adolescent childbearing since the 1970s [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Comparison of our findings with the few published studies from Ethiopia is not warranted due to methodological differences as well as the amount and nature of data used in our analyses. Nevertheless, there are indications from previous studies in Ethiopia of a decline in adolescent childbearing since the 1970s [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, socio-cultural norms to continue the family lineage and to secure one's place in the household (45) may trump the effect of any increased autonomy on the timing of children after marriage. Broader factors may also be important such as nutritional status and reproductive maturity that determine the capacity to conceive offspring (50,51). Such factors may increase the marriage to first birth interval among uneducated women, obscuring our expected relationship between increased education and the marriage to first birth interval.…”
Section: Key Findings and Policy And Research Implicationsmentioning
confidence: 99%
“…Such factors may increase the marriage to first birth interval among uneducated women, obscuring our expected relationship between increased education and the marriage to first birth interval. For example, studies in both Ethiopia (50) and Nepal (51) found that couples where the woman married at a young age delayed co-residence after marriage and hence also sexual relations, and this may increase the interval between marriage and first birth. Schoolbased sexual and reproductive health programmes such as "adolescent corners" could help girls to better negotiate the decision to get pregnant (52).…”
Section: Key Findings and Policy And Research Implicationsmentioning
confidence: 99%
“…Based on an extensive literature review and scope of the dataset, the following explanatory variables were selected and used in this study: rst sexual debut, abortion status, religion, marital status, employment status, place of residence, parity, nancial status and education. 1,9,12,22,27 Study variables characterizing adolescent childbirths were coded as described in Table 1. Table 1 Summary of study variables used in the study Hazard model: Cox proportional hazards regression with shared frailty to account for clustering at the community level was speci ed to estimate risk factors of adolescent childbirth and their 95% con dence interval.…”
Section: Study Variablesmentioning
confidence: 99%
“…In addition, the correlates of adolescent childbirths are complex and interactive. Previous studies found many predictors of adolescent childbearing predominantly in higher-income countries, 1,9,[26][27][28] however, the authors presented opposing views that could be blamed on the different study contexts, sample sizes, and methods. Although some studies in Ghana have predicted adolescent childbirths, 12,22 yet none of the studies in Ghana have fully evaluated both the individual-level determinants and community effect on adolescent childbirth.…”
Section: Introductionmentioning
confidence: 99%